Increase of Albinistic Hosts Caused by Gut Parasites Promotes Self-Transmission - Tan, Shuqian; Wang, Yang; Liu, Pingping; Ge, Yang; Li, Aomei; Xing, Yongjie; Hunter, David M.; Shi, Wangpeng (Frontiers in Microbiology, 2018)
Paranosema locustae is a gut parasite that has been applied widely in the control of grasshoppers in many parts of the world. Usually, P. locustae is transmitted horizontally via passive modes under natural conditions but in the current study, a positive transmission strategy of P. locustae was demonstrated. First, infection by P. locustae resulted in the cuticula of infected Locusta migratoria nymphs to become lighter in color: normally only a small proportion of locusts are pale with most either being partly or mostly black; but locusts infected with P. locustae became pale. And it was found that the change to pale occurred even among uninfected black and partly black nymphs reared with infected locusts. The eumelanin of the thorax and abdomen of infected individuals decreased significantly, as did the level of dopamine. In addition, there was a decrease in phenol oxidase activity and the expression of henna and pale, which are involved in the synthesis of cuticle melanin, decreased. What is the ecological significance of this increase in light-colored hosts caused by P. locustae? We discovered that light-colored locusts were more susceptible to the microsporidian pathogen than dark-colored individuals were, because of their weaker melanization. Phenol oxidase activity in pale locusts was lower than that of black locusts, but the serpin expression level of pale locusts was higher than that of black individuals. When examined for infection, it was found that initially uninfected nymphs had picked up P. locustae infections indicating that infections are readily passed from one pale locust to another. The infection rate of healthy locusts reared with light-colored locusts infected with P. locustae was 100% which was more than with black-colored ones. The increase in albinistic locusts clearly promoted the prevalence of P. locustae in the total population. In conclusion, these results elucidated a new strategy of positive self-transmission in P. locustae. Importance: Mother Nature always grants wisdom to her creatures and feeds them carefully. This wisdom is particularly apparent in the relationships between two interacting species. In this study, our team focused on the interaction between L. migratoria and P. locustae. In a previous study, it was found that L. migratoria isolate infected individuals, reducing avoiding the spread of P. locustae, in a previous study. The solitary, pale individuals infected by P. locustae were left behind as locust groups marched ahead, leading to a kind of behavioral immunity in the insects. Here, we reported that P. locustae promotes pigmentation loss in L. migratoria, causing a larger proportion of light-colored individuals, and these lighter individuals which possessed weaker immunity against pathogens. This strategy is advantageous to P. locustae, as it promotes its propagation and spread. These extraordinary abilities of L. migratoria and P. locustae have accumulated over millennia of years of interaction.